2013
DOI: 10.1371/journal.pbio.1001658
|View full text |Cite
|
Sign up to set email alerts
|

Dectin-1 Is Essential for Reverse Transcytosis of Glycosylated SIgA-Antigen Complexes by Intestinal M Cells

Abstract: This work reports the long-awaited identification of Dectin-1 and Siglec-5 as the M cell co-receptors that mediate the reverse transcytosis of secretory IgA molecules to mount a gut immune response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
140
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 149 publications
(148 citation statements)
references
References 62 publications
5
140
0
3
Order By: Relevance
“…SIgA containing complexes have been shown to be transcytosed through M cells to APCs and lymphocytes in the subepithelial dome (SED) [61,62]. Although no specific apical receptor for SIgA complexes has been described, Dectin-1 has been implicated as an important player in this process [63]. Therefore exploiting S-IgA specific epithelial receptors may offer opportunities to enhance antigen uptake following oral delivery.…”
Section: Antigen Uptake In the Gutmentioning
confidence: 99%
“…SIgA containing complexes have been shown to be transcytosed through M cells to APCs and lymphocytes in the subepithelial dome (SED) [61,62]. Although no specific apical receptor for SIgA complexes has been described, Dectin-1 has been implicated as an important player in this process [63]. Therefore exploiting S-IgA specific epithelial receptors may offer opportunities to enhance antigen uptake following oral delivery.…”
Section: Antigen Uptake In the Gutmentioning
confidence: 99%
“…Both the Cɑ1 region and glycosylation, more particularly sialic acid residues, take part in M-cell-mediated reverse transcytosis, and M cells take up SIgA via the Dectin-1 receptor, in which Siglec-5 may act as a co-receptor. 42 There are several mechanisms of targeting M cells for induction of mucosal SIgA responses in animal models. For instance, it has been demonstrated that M cell targeting mediated by a Claudin-4-specific targeting peptide enhances mucosal IgA responses above the response to nontargeted mucosal antigen, which have promise in delivery of mucosal vaccination.…”
Section: Function Of M Cellsmentioning
confidence: 99%
“…In addition to its well documented role in pathogen neutralization and clearance, 7,8,10 SIgA is endowed with the capacity to selectively retro-transport bound antigens back into intestinal Peyer's patches across microfold (M) cells 17 via the Dectin-1 receptor expressed at their surface. 18 In the subepithelial dome (SED) region, SIgA-based immune complexes associate with dendritic cells (DCs), 19 resulting in the onset of immunomodulatory types of responses. 20 Seminal papers published by the team of John Cebra more than 2 decades ago have demonstrated that at weaning, up to 70% of commensal bacteria are coated with natural SIgA in the mouse gastrointestinal tract, and that this association is instrumental to the maintenance of bacterial homeostasis; 21,22 the same holds true for pigs and calves.…”
Section: Introductionmentioning
confidence: 99%